Model Experimental Study on the Seepage and Failure Features of Tunnel under Wetting-Drying Alternation with Increasing Water Pressure - Haijian Su; Yujie Feng; Qingzhen Guo; Hongwen Jing; Wenxin Zhu (Geofluids)
Wetting-drying alternation caused by seasonal rainfall and water fluctuation has a negative effect on the rock mass. Model experiments were conducted in this paper to investigate the role of wetting-drying alternation on the seepage and failure features of a tunnel. Water-bearing structure was located in the lateral position of tunnel. The stratum thickness between the tunnel and water-bearing structure was ranged from 20 to 100 mm. The results showed that, with an increase in the wetting-drying alternation number, the pore water pressure increases gradually. The critical water pressure also increases gradually with the increasing thickness of water-resisting stratum. With the increase of the stratum thickness, the permeable area is gradually widened and the water storage capacity becomes stronger. The failure mode of water-resisting stratum under geostress and water pressure can be summarized as two types: fracture failure (thickness of 20 mm) and slippage failure (thickness between 40 and 100 mm), respectively.